The Effect of Sources/Absorber Width in Continuous Sources Atomic Absorption Spectophotometric† - Lazo, Pranvera; He, Xiwen; Shen, Hanxi (Asian Journal of Chemistry, 2010)
The effect of source/absorber width in Continuous Source Atomic Absorption Spectroscopy (CSAAS) profiles is studied to increase the intensity of atomic absorption lines. The effect of slit width in source/absorber profiles is studied too, to obtain some sharp absorption lines. Some good results are obtained when σs << σa. Some good results are achieved for lanthanide elements. The absorbances obey Beer's law and the calibration curves are linear in a good range of concentration.